HIV infection and depression. Issue 2 (30th October 2013) - Arseniou, Stylianos; Arvaniti, Aikaterini; Samakouri, Maria
<x xml:space="preserve">Abstract</x> Major depression is highly prevalent among HIV‐positive patients (HIVpp). The prevalence of depression ranges between 18% and 81%, depending on the population studied and the methodology of the study. The etiology of depression in HIVpp is likely determined by: (i) biological factors (alterations in the white matter structure, hypothalamic–pituitary–thyroid dysfunction, Tat‐protein‐induced depressive behavior); (ii) psychosocial factors (HIV stigma, occupational disability, body image changes, isolation and debilitation); (iii) history or comorbidity of psychiatric illness; and (iv) the perinatal period in HIVpp women. Symptomatology of depression differs between HIVpp and HIV‐negative patients (HIVnp). Depression may also alter the function of lymphocytes in HIVpp and decrease natural killer cell activity, contributing to the increased mortality in these patients. Selective serotonin re‐uptake inhibitors are considered the first‐line treatment. Treatment of depression can improve quality of life and lead to a better prognosis of HIV infection.